REVITALIZING PRODUCTIVE ZAKAT IN THE COVID-19 PANDEMIC ERA IN EAST JAVA - Sudirman, Sudirman; Ramadhita, Ramadhita; Bachri, Syabbul (Jurisdictie: Jurnal Hukum dan Syariah, 2021)
COVID-19 has brought significant changes in people’s lives, especially in the economic sector. As a financial tool for the people, Zakat is expected to be a source of community welfare in the pandemic era. Well-managed zakat is expected to be able to provide jobs for the affected community. This article aims to describe the revitalization of productive zakat in zakat management institutions in East Java during the COVID-19 pandemic. It is a juridical-empirical research. The study’s primary data were the results of semi-structured interviews with the Zakat Managers at BAZNAS East Java, Nurul Hayat Malang, and YDSF Malang. This study indicates that the mentioned zakat institutions have distributed zakat productively, although it has not run optimally. The problems include the lack of understanding and assistance, as well as the less varied productive zakat program. This will be easily overcome by managing productive zakat professionally involving partner institutions that are consistent in mentoring and development. This article may enrich the literature of productive zakat management and provide some recommendations to implement the zakat management more effective.COVID-19 membawa perubahan signifikan dalam kehidupan masyarakat, khususnya di sektor ekonomi. Zakat sebagai piranti keuangan umat diharapkan mampu menjadi sumber kesejahteraan masyarakat di era pandemi. Zakat yang dikelola secara produktif diharapkan mampu menyediakan lapangan pekerjaan bagi masyarakat yang terdampak. Artikel ini bertujuan mendeskripsikan revitalisasi zakat produktif di institusi pengelola zakat di Jawa Timur pada masa pandemi COVID-19. Artikel ini berdasarkan hasil penelitian yuridis-empiris. Data primer penelitian adalah hasil wawancara dengan para manajer zakat di BAZNAS Jawa Timur, Nurul Hayat Malang, and YDSF Malang. Studi ini menunjukkan bahwa lembaga zakat yang disebutkan telah mendistribusikan zakat secara produktif, meskipun belum berjalan secara maksimal. Persoalan yang dihadapi antara lain adalah lemahnya pemahaman dan rendahnya pendampingan, serta program zakat produktif yang kurang variatif. Hal tersebut akan mudah diatasi dengan pengelolaan zakat produktif secara profesional yang melibatkan lembaga mitra yang konsisten dalam pendampingan dan pengembangan. Artikel ini dapat memperkaya literatur pengelolaan zakat produktif dan memberikan beberapa rekomendasi untuk melaksanakan pengelolaan zakat secara lebih efektif.